Arduino-Based Mini Reed Switch Magnetic Sensor Media: Implementation in Physics Learning to Improve Students’ Analyzing Ability - Umi Pratiwi; Gamar Al Haddar; Muhammad Kristiawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article was to improve students' ability to analyze the viscosity material in implementing the Arduino-based MRSM (Mini Reed Switch Magnetic) teaching media. The researchers used a quasi experimental design in the form of non equivalent pre-test post-test group design. The instruments used were tests and observation sheets to obtain data. Data collection on theability to analyze through giving tests to students. Data were analyzed using descriptive statistics. The results showed an increase in the ability to analyze by 20%. The highest assessment aspect in the first aspect is the ability of students to find problems encountered and be able to distinguish problems that fit the theme. The results of this trial produce data on the implementation of learning by 98% with a reliable category. Hence, MRSM teaching media is able to improve the ability to analyze students. Keywords:Mini Reed Switch Magnetic, Sensor Media, Physics Learning